Efeitos do teor de umidade da madeira no fresamento de Pinus Elliottii - Pinheiro, Cleverson [UNESP] (2014)
Numerous factors influence the machining of wood, among them we highlight the machining parameters and the properties of this material, having the analysis of roughness as the primary tool for determining these influences. Despite the advancement of knowledge about machining of wood, there is still little information about the influence of these factors and their interactions in the machining process, since some timber industries they run into issues relating to the reduction of rework aimed at correction of roughness of machined wood parts. With this, the objective of analyzing the influence of the moisture content of the wood of Pinus elliottii, their growth rings and the machining direction in the process cutting cylindrical milling tangential, using hard metal tool. Were raised surface quality data measured in terms of roughness parameters Ra and Rt, obtained by the method of mechanical probing move, as well as power consumption and noise emission generated by the cutting process. Planning and analysis of the experiments were based on Taguchi methodology by defining three levels of moisture content (U) in % (8 ≤ U ≤ U 12; 12 < < 16; 16 ≤ U < 20), two levels to the growth rings (initial wood and latewood) and two levels to the cutting direction (up milling and down milling). The data in power consumed and noise emission were analyzed only in terms of the sense of court and the moisture content. The combination of the levels of the factors that brought the best results, in terms of surface quality, noise emission and power consumed has been the machining direction up milling, moisture content between 8 and 12 % and latewood. Statistically significant differences were determined between the levels of the three input factors analyzed by the roughness parameter Rt. Through parameter Ra was determined statistically meaningful only for cutting ... (Complete abstract click eletronic access below)